Pembangunan Masyarakat Berbasis Pariwisata: Reorientasi dari Wisata Rekreatif ke Wisata Kreatif - Poerwanto SK (Journal of Tourism and Creativity, 2019)
Abstract Today tourism has projected to become a new dynamic force to encourage global economic development. In the regional authonomy era in Indonesia tourism expected to drive the growth of others sector and to expand job opportunity, especially in creative industry. In connection with this expectation and from the reality that are several kind of tourism atractions found in different region in Indonesia, then consequently the policy of tourism development must be based on the need of community, especially local people. The concept of tourism-based community development is one of best choice for Indonesia to involve local people in the developing and managing tourism dynamic in a manner creative. Indonesia have to change the orientation of tourism development from recreative tourism to creative tourism, and it can be encourage of creativepreneur adn tourismpreneur. Keyword: community development; tourism; creativity